The Effectiveness of Role Playing Model on Upgrading Students’ Skill of Appreciation - Liza Murniviyanti; Mohsin Shaikh; Gusmaizal Syandri (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
The problem in this research was lack of students' confidence to play the role and the lack of experience of students in the experience of literature which resulted in the ability to appreciate the role play was still not satisfied. One way to tackle the problem was using the role playing method. The research method used was experiment. The population of this research was the fourth semester students of Bahasa Indonesia and Literature Education Program. Research data were obtained through practice test technique. The results showed that there was influence of role playing method on role playing ability in accordance with drama script written by students.